Proceedings of the 2021 Conference on Empirical Methods in Natural Language Processing 2021
DOI: 10.18653/v1/2021.emnlp-main.281
|View full text |Cite
|
Sign up to set email alerts
|

Self-Supervised Curriculum Learning for Spelling Error Correction

Abstract: Spelling Error Correction (SEC) that requires high-level language understanding is a challenging but useful task. Current SEC approaches normally leverage a pre-training then fine-tuning procedure that treats data equally. By contrast, Curriculum Learning (CL) utilizes training data differently during training and has shown its effectiveness in improving both performance and training efficiency in many other NLP tasks. In NMT, a model's performance has been shown sensitive to the difficulty of training example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Depending on whether any (or both) of the two components are designed with the aid of human expertise (or data-driven approaches), a strategy can be classified as either pre-defined or automatic CL. Take difficulty measurer as an example, Platanios et al (2019) developed a pre-defined strategy in which the difficulty of input text was determined by using its length as a proxy (i.e., the longer the input text, the higher difficulty it has), while Gan, Xu, and Zan (2021) proposed an automatic strategy in which the difficulty was measured by calculating its training loss in a specific epoch.…”
Section: Curriculum Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on whether any (or both) of the two components are designed with the aid of human expertise (or data-driven approaches), a strategy can be classified as either pre-defined or automatic CL. Take difficulty measurer as an example, Platanios et al (2019) developed a pre-defined strategy in which the difficulty of input text was determined by using its length as a proxy (i.e., the longer the input text, the higher difficulty it has), while Gan, Xu, and Zan (2021) proposed an automatic strategy in which the difficulty was measured by calculating its training loss in a specific epoch.…”
Section: Curriculum Learningmentioning
confidence: 99%
“…To answer the above question, we centered our work on the design of the two key components of a CL strategy (Wang, Chen, and Zhu 2021;Liu et al 2018): (i) difficulty measurer, which determines the relative difficulty level of a training data sample; and (ii) training scheduler, which determines the data subset that should be input to a model in a specific training epoch based on the evaluation from the difficulty measurer. Inspired by previous works on proposing effective CL strategies in the broader NLP research (e.g., Spelling Error Correction (Gan, Xu, and Zan 2021) and Natural Answer Generation (Liu et al 2018)) as well as the works on automatically characterizing textual data in education, we devised two types of CL strategies in this work, i.e., pre-defined and automatic, which are grouped according to whether any or both of the two key components described above are pre-defined by human experts or automatically learned in a data-driven fashion. It should be noted that these naming terminologies are in line with those summarized by Wang, Chen, and Zhu (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, researchers frequently rely on synthetic data to generate these datasets. Furthermore, with the increase in the number of synthetic data studies based on self-supervised learning [20,21,22] and the demonstrated effectiveness of exponentially increasing the amount of data through scaling laws [23,24,25], there is a pressing need for in-depth validation of models trained exclusively on synthetic data.…”
Section: Usermentioning
confidence: 99%
“…From an educational point of view, interpretability is improved by adding text and examples for language learners expanding the reason for correction together [15]. Self-Supervised Curriculum Learning is applied to measure data difficulty through training loss and train the model to increase performance [16]. Applying a contrastive learning approach to the GEC model improves performance for low error density domains [17].…”
Section: Related Workmentioning
confidence: 99%